2009
DOI: 10.14227/dt160109p35
|View full text |Cite
|
Sign up to set email alerts
|

Goodness-of-Fit Model-Dependent Approach for Release Kinetics of Levofloxacin Hemihydrates Floating Tablet

Abstract: The objective of this work was to develop floating levofloxacin tablets and to understand the kinetics of drug release by applying mathematical and model-dependent approaches. Nine formulations of floating tablets were prepared by the direct compression method using Gelucire 43/01 (hydrophobic) and hydroxypropyl methylcellulose (hydrophilic) as matrix-forming excipients. The in vitro drug release was studied in pH 1.2 HCl using USP dissolution Apparatus 2 at 50 rpm. Zero-order, first-order, Higuchi, Hixson-Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…In the present study, an attempt was made to design Carbidopa and Levodopa ER Tablet and its release profile was interpreted with various mathematical models [4].…”
Section: Formulation Of Carbidopa-levodopa Er Tablets 50 Mg/200 Mg [3]mentioning
confidence: 99%
“…In the present study, an attempt was made to design Carbidopa and Levodopa ER Tablet and its release profile was interpreted with various mathematical models [4].…”
Section: Formulation Of Carbidopa-levodopa Er Tablets 50 Mg/200 Mg [3]mentioning
confidence: 99%
“…In contrast to most conventional floating systems (including gas-generating ones), these minitablets floated immediately upon contact with the release medium showing zero lag time in floating behavior because the low density was prevailed from the beginning (t ¼ 0). Thakkar et al (2009) reported that in case of a gelucire based floating tablet, incorporation of HPMC and sodium bicarbonate is essential to achieve desirable floating. But in the present research, we have achieved desirable floating without any gas generating agent by compressing these gelucire-based granules into minitablets of 3 mm diameter but when the same formulation was compressed into a tablet of 6 mm diameter they did not exhibit floating.…”
Section: In Vitro Buoyancy and Percent Buoyancymentioning
confidence: 99%
“…Media disolusi yang digunakan adalah larutan HCl 0,1 N sebanyak 900 ml pada suhu 37±0,5ºC [8]. Sampel (5,0 ml) diambil setiap interval waktu 10, 20, 30, dan 45 menit kemudian disaring dengan kertas saring 0,45 µm.…”
Section: Evaluasi Tabletunclassified